Tinjauan Efektivitas Penampang Drainase Akibat Akumulasi Sedimen (Kolmatase) di Kawasan Jalan Selomangleng - Afifa Zahra Qurratu’ain; Sony Susanto (Jurnal Talenta Sipil, 2026)
Urban drainage systems often experience performance degradation due to sediment accumulation (colmation), even when channel dimensions comply with design standards. This study aims to evaluate the effectiveness of the drainage cross-section affected by colmation in the Selomangleng Road area, Kediri City, and to assess the potential of an additional infiltration system as a supporting solution. The research employed a quantitative–analytical approach using hydraulic analysis based on the Manning equation to compare flow capacity under design and existing (colmated) conditions. The results indicate that channel capacity decreased from 0.62 m³/s under design conditions to 0.26 m³/s under existing conditions, resulting in a capacity loss of 0.36 m³/s and a cross-sectional effectiveness of approximately 42%. As a supplementary analysis, an infiltration trench system was designed along a total length of 350 m on both sides of the channel. With a total infiltration area of 350 m² and alluvial soil permeability of 1 × 10⁻⁵ m/s, the system provides an infiltration discharge of 0.0035 m³/s and an effective storage volume of 73.5 m³. The findings demonstrate that colmation is the primary factor reducing drainage performance, while the infiltration trench functions as a complementary solution to attenuate peak discharge and delay runoff when combined with regular channel maintenance.